2019
DOI: 10.4236/oalib.1105837
|View full text |Cite
|
Sign up to set email alerts
|

Merger and Acquisition Patterns and Trends: An Evidence of an Emerging Economy, Turkey 2014-2018

Abstract: This study aims to provide contemporary and comparative analysis on mergers and acquisitions (M & As) activities that Turkish companies are involved between 2014-2018, by analyzing trends in deal number, deal volume activity and characteristics, and an attempt to explore the challenges, issues and implications opposing companies in M & As in Turkey. The study follows a qualitative method for data collection and analysis, using secondary data and the annual merger and acquisitions review reports of Deloitte 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This makes acquisitions important for emerging markets. As one of the leading emerging markets in the world, Turkey has seen a great increase in acquisition activity (Alhanhanah, Akbalik, and Akosile, 2019;Oelger and Schiereck, 2011), which creates a need to analyze acquisition activity in this market.…”
Section: Discussionmentioning
confidence: 99%
“…This makes acquisitions important for emerging markets. As one of the leading emerging markets in the world, Turkey has seen a great increase in acquisition activity (Alhanhanah, Akbalik, and Akosile, 2019;Oelger and Schiereck, 2011), which creates a need to analyze acquisition activity in this market.…”
Section: Discussionmentioning
confidence: 99%
“…The study also found that that the negative relation between target country-specific uncertainty and cash payment weakened with larger differences in power distance between host and home countries. Alhanhanah, Akbalik, and Akosile, (2019) examined the trends of M&A in Turkey covering the period 2014-2018. They found that the election transition year of 2014 affected the volume and value of M&A.…”
Section: Ad-ministermentioning
confidence: 99%